Dizziness and neck pain: a perspective on cervicogenic dizziness exploring pathophysiology, diagnostic challenges, and therapeutic implications - De Hertogh, Willem; Micarelli, Alessandro; Reid, Sue; Malmström, Eva-Maj; Vereeck, Luc; Alessandrini, Marco (Frontiers in Neurology, 2025)
Dizziness and vertigo affect up to 20% of adults annually. Cervicogenic dizziness (CGD), a debated clinical entity, is characterized by dizziness associated with cervical pain or dysfunction, stemming from altered proprioceptive input from the cervical spine. Despite its recognition in clinical practice, CGD remains controversial due to its reliance on exclusionary diagnosis and the absence of specific diagnostic criteria or gold-standard tests. This perspective explores the pathophysiology of CGD, emphasizing the sensory mismatch theory, where disrupted cervical proprioception interacts maladaptively with vestibular and visual systems, leading to postural instability and dizziness. Central mechanisms, including sensory reweighting and maladaptation, further complicate symptom resolution, particularly in the context of chronic cervical dysfunction. Current diagnostic approaches provide insights but lack specificity. Management strategies, including manual therapy and sensorimotor exercises, show promise in alleviating symptoms by targeting cervical dysfunction and enhancing proprioceptive integration. However, these interventions highlight the need for an integrated approach that addresses both cervical and vestibular contributions to dizziness. This paper underscores the importance of advancing CGD research, particularly understanding central maladaptation mechanisms. By bridging gaps in clinical and research knowledge, a more comprehensive framework for diagnosing and managing CGD can emerge, benefiting patients with persistent dizziness and cervical involvement.